PENGARUH KEBIJAKAN HUTANG, PROFITABILITAS, DAN FIRM SIZE TERHADAP NILAI PERUSAHAAN DENGAN GCG SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BEI PERIODE 2022–2024) - Ferdy Fachrial Yusuf; Rico Wijaya; Misni Erwati (Komunitas Manajemen Kompetitif, 2026)
This study aims to analyze the effect of debt policy, profitability, and firm size on firm value with Good Corporate Governance (GCG) as a moderating variable in mining companies listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. This research employs a quantitative approach using secondary data obtained from the companies’ annual reports. The sample was selected using a purposive sampling technique and analyzed using the Structural Equation Modeling–Partial Least Square (SEM-PLS) method with WarpPLS 7.0 software. The variables used in this study include debt policy, profitability, firm size, firm value, and Good Corporate Governance. This study is expected to provide empirical evidence regarding the factors influencing firm value and the role of Good Corporate Governance in moderating the relationship among these variables